Influence of Atmospheric Corrosion on the Service Life of Steel Sheets - Marian Bursak; Jan Michel (Communications - Scientific letters of the University of Zilina, 2006)
The paper analyses the influence of the duration of atmospheric corrosion on basic mechanical and fatigue properties of steel sheet 2.16–4.46 mm thick, made of low-carbon steel with higher atmospheric corrosion resistance. A decrease of mechanical properties as a function of the exposure time is mainly due to a weight loss and the fatigue limit decrease under flat bending is due to increased surface roughness weathering steel too. The fatigue limit is a crucial characteristic for the service life of products, since after 5 years of exposure it decreased by 36%, while the ultimate tensile strength decreased by as little as 8%.